Astragaloside IV Improves High-Fat Diet–Induced Hepatic Steatosis in Nonalcoholic Fatty Liver Disease Rats by Regulating Inflammatory Factors Level via TLR4/NF-κB Signaling Pathway - Liu, Ying-Li; Zhang, Qiu-Zan; Wang, Yan-Rong; Fu, Li-Na; Han, Jing-Shu; Zhang, Jing; Wang, Bang-Mao (Frontiers in Pharmacology, 2021)
Objective: Astragaloside IV(AS-IV) is the primary bioactive component purified from Astragalus membranaceus which isone of the traditional Chinese medicines. Researches found that AS-IV has significant pharmacological effects on focal cerebral ischemia/reperfusion, cardiovascular disease, pulmonary disease, liver cirrhosis and diabetic nephropathy, but little is known about the effects of AS-Ⅳ on non-alcoholic fatty liver disease (NAFLD).In this study,we investigated whether AS-Ⅳhas beneficial effects on NAFLD in rats and its potential mechanisms. Methods: Male SD rats were fed with high-fat-diet (HFD) for 12 weeks to establish NAFLD rats model, then the rats were dived into 4 groups. The control group rats were fed with HFD for 12 weeks, and then were given normal saline (1.0 ml•kg-1•d-1) by intragastric administration for 4 weeks. The AS-Ⅳ-L, AS-Ⅳ-M and AS-Ⅳ-H group were treated with 20,40 and 80mg•kg-1•d-1 of AS-Ⅳ by intragastric administration for 4 weeks. Then, we detect the rat serum liver function (ALT, AST, TG, TC), immunological indexes (IL-6, IL-8,TNF-α) and liver histopathology(NAFLD activity score), measure the mRNA and protein expression of TLR4/MyD88 pathway in rat liver tissue. Results: We found AS-Ⅳ significantly reduce serum levels of AST, ALT, TG, TNF-α, IL-6 and IL-8in NAFLD rats, and down-regulate the expression of TLR4 mRNA, MyD88 mRNA, NF-κB mRNA and their proteins in liver tissue. Moreover, AS-Ⅳ could significantly reduce NAFLD activity score of NAFLD rats liver. Conclusion:In this study, we demonstrate that AS-Ⅳ exerted protective effect on NAFLD, inhibiting the levels of TNF-α, IL-6, IL-8 and down-regulating the TLR4, MyD88 and NF-κB expression in liver tissue of rats.